The relationship between body weight and body condition score in Karacabey merino ewes - (:unkn) unknown (My University, 2008)
Canlı ağırlık ve Vücut Kondüsyon Puanı (VKP) arasındaki ilişkiler koç katımı, kuzulama ve sütten kesim gibi üç farklı fizyolojik dönemde incelenmiştir. Marmara Hayvancılık Araştırma Enstitüsü'nde yetiştirilen 317 baş Karacabey Merinosu koyun çalışmanın hayvan materyalini oluşturmuştur. Her dönemdeki canlı ağırlık ve vücut kondüsyon puanı arasındaki regresyon analizi sonuçları için sırası ile CA=50.072+5.630*VKP, CA=50.914+5.722*VKP, CA=49.807+7.659* VKP denklemleri kurulmuştur. Benzer şekilde aralarındaki korelasyonlar (r) sırası ile 0.627, 0.651, 0.709 ve istatistiksel olarak önemli olmuştur (P<0.01). Vücut Kondüsyon Puanındaki bir birimlik değişime eşdeğer olan canlı ağırlıklar koç katımında 5.630, kuzulama da 5.722 ve sütten kesimde 7.659kg olarak belirlenmiştir (P<0.01).

The relationships between Body Condition Scores (BCS) and Body Weights (BW) have been investigated in three different physiological status such as mating, lambing and weaning time of ewes. The data were collected from 317 Karacabey Merino ewes in different age groups which were bred in Marmara Animal Research Institute. The results obtained from the regression analyses on BCS and LW for the status were based on the equations like LW=50.072+5.630*BCS, LW=50.914+5.722*BCS, LW=49.807+7.659*BCS respectively. The correlations (r) established by similar methods were 0.627, 0.651, 0.709 and statistically significant (P<0.01). The regression coefficients of BCS on BW were 5.630kg, 5.722kg, 7.659kg at mating, lambing, weaning respectively and also significant (P<0.01).
Karacabey merinosu koyunlarda canlı ağırlık ve vücut kondüsyon puanı arasındaki ilişkiler
Keywords: Ziraat Mühendisliği